Airpower reborn the strategic concepts of John Warden and John Boyd - Olsen, John Andreas 1968- (Naval Institute Press, 2015)
Airpower Reborn offers a conceptual approach to warfare that emphasizes airpower's unique capability to achieve strategic effects. Six world-leading theorists argue that a viable strategy must transcend the purely military sphere, view the adversary as a multi-dimensional system, and pursue systemic paralysis and strategic effects rather than military destruction or attrition.